Fakosklerektomia głęboka z implantem akrylowym – opis metody - Rękas, Marek; Wierzbowska, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
The surgical technique of deep sclerectomy with acrylic implant was described. The indications, advantages and possible complications of the method were presented.